The relationship between mean platelet volume lymphocyte ratio and collateral circulation in patients with chronic total coronary occlusion - Niu, Ming-Hui; Liu, Peng-Hui; Liu, Ze-Hua; Zhu, Jun-Wei; Guo, Rong; He, Fei (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: To correlate mean platelet volume lymphocyte ratio (MPVLR) and coronary collateral circulation (CCC) in patients with chronic total occlusion (CTO). Methods: A total of 643 patients who were hospitalized at a single large academic medical center from January 2020 to October 2021 and had CTO lesions in at least one major coronary artery confirmed by coronary angiography were retrospectively analyzed. Patients were divided according to the Rentrop criteria into poorly formed CCC (Rentrop 0-1, n =235) and well-formed CCC (Rentrop grade 2-3, n=408) groups. Mean platelet volume lymphocyte ratio (MPVLR) was calculated from routine laboratory data (MPV divided by lymphocyte count). The clinical data of the two groups were compared, and relationships between MPVLR and CCC formation were analyzed. Results: The MPVLR of patients with poorly formed CCC was significantly higher than that of patients with well-formed CCC (7.82±3.80 vs 4.84±1.42, P < 0.01). The prevalence of diabetes mellitus and C-reactive protein levels were significantly higher in the poor CCC group than in the good CCC group (P < 0.01), while the proportions of patients with CTO or multivessel lesions in the right coronary artery were significantly lower in the poor CCC group than in the good CCC group (P < 0.01). Multivariate logistic regression analysis identified MPVLR (OR:2.242, 95%CI: 1.552-3.239, P < 0.01), C-reactive protein level (OR: 1.029, 95%CI: 1.001-1.058, P < 0.05), a history of diabetes mellitus (OR: 2.237, 95%CI: 1.445-3.463, P < 0.01) and right coronary CTO ratio (OR: 0.278, 95%CI: 0.177-0.436, P < 0.01) as independent risk factors for CCC formation. The area under the ROC curve of MPVLR for predicting poorly formed CCC was 0.82 (95%CI: 0.784-0.855, P< 0.01), the best cut-off point was 6.02 and the sensitivity and specificity of MPVLR for predicting poorly formed CCC were 72.3% and 82.4%, respectively. Conclusions: In patients with coronary CTO, MPVLR was negatively correlated with CCC and a high MPVLR level was an independent predictor of poorly formed CCC.